2018
DOI: 10.33961/jecst.2018.9.4.330
|View full text |Cite
|
Sign up to set email alerts
|

Structural Effect of Conductive Carbons on the Adhesion and Electrochemical Behavior of LiNi0.4Mn0.4Co0.2O2 Cathode for Lithium Ion Batteries

Abstract: The adhesion strength as well as the electrochemical properties of LiNi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…3c) confirm that in all cases the expected redox processes occur in NMC (hexagonal H1 ↔ monoclinic M around 3.7 V). [39][40][41][42][43][44] The electrochemical performance of heat-treated composites reveals that the heat treatment significantly alters the composite electrochemical performance with all grades of carbons. Figure 3d shows the second charge-discharge curve of the heated composites at C/20, where it can be observed that 500-KB composite has a significant drop in capacity (more than 20%) along with an enhanced polarization and a more slopy discharge curve compared to the corresponding mixed composite.…”
Section: Resultsmentioning
confidence: 99%
“…3c) confirm that in all cases the expected redox processes occur in NMC (hexagonal H1 ↔ monoclinic M around 3.7 V). [39][40][41][42][43][44] The electrochemical performance of heat-treated composites reveals that the heat treatment significantly alters the composite electrochemical performance with all grades of carbons. Figure 3d shows the second charge-discharge curve of the heated composites at C/20, where it can be observed that 500-KB composite has a significant drop in capacity (more than 20%) along with an enhanced polarization and a more slopy discharge curve compared to the corresponding mixed composite.…”
Section: Resultsmentioning
confidence: 99%
“…Figure S2 displays the surface morphologies of the SWCNTs (sub-carbon additive) and GO nanosheets (coating material). The SEM image of the as-received SWCNTs (Figure S2A) reveals a long fibrous (nanowire-like) morphology with a smooth surface, potentially effective for conducting electrons over a wide range due to the ordered graphitic planes of the CNT network. , The SEM image of the as-received GO nanosheets reveals a multilayer structure (Figure S2B); they further exfoliated into transparent GO nanosheets with a few layers (see the TEM image in Figure S2C) upon dilution of the as-received GO solution and subsequent ultrasonication. These two-dimensional (2D) GO nanosheets would presumably form a strong and thin protective layer on the LNMO surface, stabilized through electrostatic or hydrogen bonding interactions. , Figure C,D presents SEM images of the pristine LNMO and 0.1%SWCNT-LNMO electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…Conductive carbon additives used in electrode fabrication have also played another vital role: enhancing the electronic conductivity of the active materials in LIBs. Most carbon materials, including acetylene black, super P, Ketjen black, graphite, carbon nanotubes (CNTs), and vapor-grown carbon fibers (VGCFs), have been explored as conductive additives in the preparation of LIB electrodes due to their excellent electronic conductivities and thermal stabilities. , These conductive additives tend to wrap up the grains of the active materials and induce uniform charge distribution to decrease the contact and internal resistances of the electrodes, thereby improving the high-rate performance. Nevertheless, the feature sizes and morphologies of these conductive additives can affect the adhesion and electrochemical performance of the high-voltage cathode materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations